Services trade liberalization at the regional level: Does Southern and Eastern Africa stand to gain from EPA negotiations? - Marion Jansen (World Trade Organization (WTO), 2006)
This paper discusses the opportunities and challenges for Southern and Eastern African ACP countries of services negotiations in the context of European Partnership Agreements. The paper provides an overview of existing flows in services from and to Southern and Eastern Africa, an overview that suffers from the paucity of relevant data. Given the significant differences among services sectors, the paper provides a separate discussion for several of them, including financial services, tourism and business services. The latest developments in each sector are described and the issues that are at stake in trade negotiations. In this context the competitive position of Southern and Eastern African countries is compared with the position of the European Union and other global players. The paper attempts to identify possible export opportunities for Southern and Eastern African ACP countries and discusses the advantages and disadvantages of giving preferential access to EU suppliers in those services sectors where African countries are likely to import. Particular attention is paid to the role of mode 4 in the discussed services sectors.
Keywords: F13; F15; O19; 330; regional trade agreements; trade in services; GATS; Africa; Handelsregionalismus; Internationaler Dienstleistungsverkehr; GATS; Südliches Afrika; Ostafrika